Development of a tissue-specific bioscaffold for intestinal stem cell culture - Kakar, Sachin; Derouet, Mathieu F.; Zhang, Liyue; Gillis, Connor J.; Larsen, Frederikke; Paul, Arghya; Flynn, Lauren E.; Asfaha, Samuel (PloS one, 2025)
The generation of a tissue-specific intestinal hydrogel derived from the native intestine has the potential to support and promote the growth of intestinal organoids. In this study, we aimed to develop hydrogels derived exclusively from intestinal extracellular matrix (ECM) or composites comprised of intestinal ECM combined with alginate that allow for greater tuning of the hydrogel properties. A novel mouse intestinal decellularization protocol was developed and the ECM characterized. Our analyses demonstrate that our protocol effectively removed cellular and nuclear content while preserving key ECM components including collagens, glycosaminoglycans, fibronectin and laminin. When the decellularized small intestine (DSI) was used to generate hydrogels, the resulting ECM showed bioactivity as demonstrated by metabolic and pro-proliferative effects on NIH 3T3 murine fibroblasts. Importantly, our novel DSI hydrogels also supported murine intestinal and colonic organoid growth similar to Matrigel® controls. These studies demonstrate that murine tissue-specific DSI hydrogels can provide a supportive environment for the culture of intestinal and colonic organoids in vitro .